1996
DOI: 10.1097/00001648-199601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Melanoma Linked to Occupations and Chemical Exposures

Abstract: We conducted a case-control study in the western United States to determine the relation between occupations or chemical exposures and increased risk of uveal melanoma. Among men (221 patients, 447 controls), we found increased risks for occupational groups who had intense exposure to ultraviolet light [odds ratio (OR) = 3.0; 95% confidence interval (CI) = 1.2-7.8], welding exposure (OR = 2.2; 95% CI = 1.3-3.5), and asbestos exposure (OR = 2.4; 95% CI = 1.5-3.9 for most likely exposed). The highest odds ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
59
1
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 20 publications
3
59
1
1
Order By: Relevance
“…A recently published case -control interview study from Germany reported a significant four-fold increased risk of malignant melanoma of the eye associated with the use of radiofrequency (RF) transmitting devices, including mobile telephones (Stang et al, 2001). These data were generally consistent with a previous case -control investigation linking uveal melanoma with occupations involving radiofrequency exposures to radar and microwaves (Holly et al, 1996). To evaluate whether radiofrequency exposure might increase the risk of ocular cancer, we compared incidence data from the Danish Cancer Registry with information on the number of cellular telephone users in Denmark over the past two decades.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…A recently published case -control interview study from Germany reported a significant four-fold increased risk of malignant melanoma of the eye associated with the use of radiofrequency (RF) transmitting devices, including mobile telephones (Stang et al, 2001). These data were generally consistent with a previous case -control investigation linking uveal melanoma with occupations involving radiofrequency exposures to radar and microwaves (Holly et al, 1996). To evaluate whether radiofrequency exposure might increase the risk of ocular cancer, we compared incidence data from the Danish Cancer Registry with information on the number of cellular telephone users in Denmark over the past two decades.…”
supporting
confidence: 77%
“…of mobile telephone subscribers Figure 1 Age-standardized World Standard Population (WSP) annual incidence (cases per 100 000) of ocular malignant melanoma in Denmark 1943 -1996 and number of subscribers to cellular telephones, Denmark 1982-1996.…”
Section: Epidemiologymentioning
confidence: 99%
“…However, the small numbers of subjects with iris and conjunctival melanoma preclude certainty about risks associated with exposure to UVR. 2 New England Exposure to welding arcs 15 years before diagnosis 1.3 (0.5-3.1) 2 Ajani et al 5 New England Occupationally exposed to welding arc 15 years before diagnosis 1.0 (0.5-2.1) 4 Siemiatycki et al 6 Montreal Any occupational exposure to arc welding fumes 8.3 (2.5-27.1) 5 Any occupational exposure to gas welding fumes "No association" Holly et al 3 San Francisco History of welding burn, sunburn to eye, or snow blindness 7.2 (2.5-20.6) 3 Holly et al 4 San Francisco Men occupationally exposed to welding (self-welding or in proximity of others) for Ն 3 hr/week for Ն 6 months 2.2 (1.3-3.5) 6 Men occupationally exposed to welding for Ն 11 years 1.9 (1.0-3.6) 6 Men first occupationally exposed to welding Ն 30 years before diagnosis 2.1 (1.1-4.0) 6 Guenel et al 7 France Cumulative occupational exposure to artificial UVR (job exposure matrix) 5.5 (1.8-17.2) 7…”
Section: Discussionmentioning
confidence: 99%
“…Men employed as a welder or sheet metal worker for Ն 20 years 11.5 (2.4-55.5) 8 Seddon et al 2 included choroid and ciliary body only; Holly et al 4 also included conjunctiva. Same subjects used in Seddon et al 2 and Ajani et al 5 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation